História evolutiva de Conepatus (Carnivora: Mephitidae) : padrões biogeográficos de diversificação, investigação filogenética e revisão taxonômica do gênero - Rodrigues, Manoel Ludwig da Fontoura (2013)
Conepatus (Mammalia: Carnivora) comprises one of the least known groups of Neotropical mammals. Despite its broad distribution, ranging from southern North America to southernmost South America, few studies have been conducted on this genus. The lack of knowledge regarding the ecology, morphology and distribution of different populations hampers comparative studies, resulting in much of the group's diversity remaining unknown. The most basic problem, however, seems to be the lack of studies regarding the evolutionary history and phylogenetic relationships among its populations, which are the main grounds for modern taxonomic classifications. A solid taxonomic arrangement is critical, since it is the principie that guides the description of ali other aspects of a given population. Finaily, understanding the evolutionary history of a taxon is important not only due to taxonomic concerns, but also because it is the cumulative knowledge on the diversification of different groups that allows the description of major biogeographic patterns. Attempting to shed light on several of these aspects, this study investigated phyiogenetic patterns, evolutionary history, population structure, morphological variation and general distribution of Conepatus, which altogether led to a taxonomic revision. To accomplish this, molecular analyses were performed, based on 1,902 base pairs of the mitochondrial DNA and eight microsatellite loci. We also conducted two types of morphological surveys. The first one was based on a panel of 29 craniodental measurements, while the second one investigated the differentiation of external body features among previousiy identified populations. Finally, we performed an extensive search for geographic records in original publications and scientific collection databases. Overall, the results indicated that Conepatus is a highly structured genus, encompassing at least 10 distinct geographic groups. In addition, at least some of these groups presented a noticeabie levei of morphological differentiation in terms of general body aspects, which reinforces the identified population structure. With respect to distributional aspects, Conepatus seems to inhabit almost exclusively open habitats and dry forests, rarely being found in moist dense forests. Some distributional discontinuities could be identified, which may be directly linked to the complete or partial isolation between groups. The evolution of the genus is complex, and appears to be linked to broad biogeographic patterns. The coalescence of Central and South American groups was estimated in ca. 3.2 million years ago (MYA), supporting the hypothesis that this genus colonized South America right after the complete closure of the Panama Isthmus, ca. 2.8 MYA, during the Great American Biotic Interchange. The coalescence of the South American populations, however, is far more recent (ca. 0.85 MYA), suggesting a complex evolutionary history, possibiy linked to the peculiar vegetation dynamics that took place in South America during the cycles of Pleistocene ice ages. Finally, a new taxonomic arrangement is proposed, suggesting that ali 10 identified groups could be elevated to the rank of species, due to the observed pattern of differentiation among these lineages.